2013
DOI: 10.2298/zmspn1324013k
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus species as mycotoxin producers in agricultural products in central Europe

Abstract: Aspergillus species are able to produce a range of mycotoxins, includ­ing e.g. aflatoxins, ochratoxins, fumonisins and patulin. Aflatoxins are mainly produced by members of Aspergillus section Flavi, and they contaminate various agricultural products in several parts of the world. Several recent reports have indicated that aflatoxin-producing fungi and consequently aflatoxin contamination occur in agricultural commodities in a number of European countries which have not been faced with this problem befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Alternaria alternata f. sp. lycopersici produces small amounts of FB1 (Abbas & Riley, ), while the contribution of Aspergillus awamori and Aspergillus niger might reach considerable amounts (Frisvad, Smedsgaard, Samson, Larsen, & Thrane, ; Varga et al., ; Perrone et al., ; Kocsub'e et al., ). A. niger is an important pathogen of grapevine (Varga et al., ; Perrone et al., ) and producer of various fumonisins (fumonisins B 1 to B 4 and fumonisin B 6 ; for example, Frisvad et al., ; Varga et al., ; Scott, ).…”
Section: Fumonisins In Foodstuffs and Agricultural Commoditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternaria alternata f. sp. lycopersici produces small amounts of FB1 (Abbas & Riley, ), while the contribution of Aspergillus awamori and Aspergillus niger might reach considerable amounts (Frisvad, Smedsgaard, Samson, Larsen, & Thrane, ; Varga et al., ; Perrone et al., ; Kocsub'e et al., ). A. niger is an important pathogen of grapevine (Varga et al., ; Perrone et al., ) and producer of various fumonisins (fumonisins B 1 to B 4 and fumonisin B 6 ; for example, Frisvad et al., ; Varga et al., ; Scott, ).…”
Section: Fumonisins In Foodstuffs and Agricultural Commoditiesmentioning
confidence: 99%
“…Raisins of various origins are targeted by several genera of molds. Fumonisin production can be attributed to Aspergillus niger and A. awamori (Varga et al., ; Kocsubé et al., ). The low water content of these products does not prevent the growth of pathogens, because Aspergillus isolates have been shown to produce huge amounts of toxins at reduced water activity.…”
Section: Fumonisins In Foodstuffs and Agricultural Commoditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data published in the most recent decade [23][24][25][26][27][28] confirmed the presence of toxigenic strains of A. flavus and aflatoxin contamination in agricultural products and soil samples in Hungary and other neighbouring countries of the Pannonian agro-ecological zone.…”
Section: Pathogen Occurrencementioning
confidence: 82%
“…These years were humid and moderately warm; therefore, the fungus was able to infect silks and, subsequently, cobs [ 30 ]. Kocsubé et al [ 31 ] isolated and identified a large number of A. flavus in the southern part of Hungary, and approximately 25% of the isolates were able to produce aflatoxins. Dobolyi et al [ 32 ] established that the toxigenic Aspergillus species are also present in all Hungarian agricultural areas.…”
Section: Introductionmentioning
confidence: 99%